.: THE EFFECTIVENESS OF A MULTIDISCIPLINARY APPROACH IN THE MANAGEMENT OF HIGH-RISK PREGNANCIES, INCLUDING THE ROLES OF GYNECOLOGISTS, OBSTETRICIANS, SURGEONS, NURSES, PHARMACISTS, RESPIRATORY PHYSICAL THERAPISTS, AND SOCIAL SERVICE PROVIDERS IN OPTIMIZING MATERNAL AND FETAL OUTCOMES - Maya Moutaz Albezreh; Mohammed Radhi Hassan Alessa; Hassan Ahmed Almohammedali; Faisal Abbad Alabbad; Osama Abdulrahman M Alsarawi; Mohammed Hussain Alobud; Alali, Batool Ali S; Abdulaziz Ali Bosanah; Manal Abdullah Dwerg Alharbi; Zahra Ahmed Aljaman; Ali Ahssan Al Shawarib; Fahad Abdulrahman Alharthi; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
High-risk pregnancies present significant challenges to maternal and fetal health, requiring a comprehensive and coordinated approach to management. This review article explores the effectiveness of a multidisciplinary approach in addressing the complex needs of high-risk pregnancies, with a focus on the roles of various healthcare professionals in optimizing maternal and fetal outcomes. The involvement of gynecologists, obstetricians, surgeons, nurses, pharmacists, respiratory physical therapists, and social service providers in the care of high-risk pregnancies is crucial for ensuring the best possible outcomes for both mother and baby.The multidisciplinary team collaborates to develop individualized care plans that address the specific needs and risks associated with each high-risk pregnancy. Gynecologists and obstetricians play a central role in the medical management of these pregnancies, providing specialized care and monitoring throughout the antenatal period. Surgeons may be called upon to address obstetric complications that arise during pregnancy or delivery, ensuring the safety of both mother and baby.Nurses are essential members of the multidisciplinary team, providing ongoing support, education, and monitoring to high-risk pregnant women. Pharmacists play a critical role in medication management, ensuring that pregnant women receive safe and effective treatments for their conditions. Respiratory physical therapists may be involved in cases where respiratory complications arise, providing interventions to optimize lung function and support maternal well-being.Social service providers play a key role in addressing the psychosocial needs of high-risk pregnant women, providing support, counseling, and resources to promote overall well-being. By working together, these healthcare professionals can address the complex needs of high-risk pregnancies comprehensively, leading to improved maternal and fetal outcomes.